High-permeability grouting material for treating leakage water diseases and preparation method of high-permeability grouting material

By optimizing the material formulation and preparation process, a high permeability grouting material for water leakage treatment was developed, which solved the problem of poor results of existing materials under fine cracks and complex geological conditions, and achieved efficient and environmentally friendly water leakage treatment effect.

CN119841606AActive Publication Date: 2025-04-18CHANGCHUN URBAN CONSTR & MAINTENANCE GRP CO LTD

Patent Information

Application Number
CN202510091879.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing leak treatment materials are not effective when facing fine cracks or complex geological conditions, and there are problems such as high viscosity, poor permeability, high cost, high construction difficulty and poor environmental adaptability.

Method used

A highly permeability grouting material is used, and its formulation includes type 525 sulfonaluminate cement, fly ash, isophorone diisocyanate, polyvinyl acetate and nanomodifier. By optimizing the material formulation and preparation process, the permeability, fluidity and curing properties of the material are improved.

Benefits of technology

The high-permeability grouting materials have been achieved with low viscosity, high permeability, rapid curing, high strength, environmental protection and strong adaptability, which has significantly improved the construction efficiency and quality of water leakage treatment in underground engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841606A_ABST
    Figure CN119841606A_ABST
Patent Text Reader

Abstract

The invention discloses a high-permeability grouting material for treating leakage water diseases and a preparation method of the high-permeability grouting material, and belongs to the technical field of energy-saving and environment-friendly building materials. According to the material, 525 type sulphoaluminate cement, fly ash, isophorone diisocyanate, polyvinyl acetate and a nano modifier are used as main raw materials, and the fluidity, permeability and solidified body performance of the grouting material are remarkably improved by optimizing the formula proportion and the preparation process. The nano modifier enhances the compactness and interface bonding force of the slurry through efficient dispersion and cross-linking reaction, the porosity is effectively reduced, and the impermeability and compressive strength are improved. The preparation method comprises the steps of raw material weighing and pretreatment, mixing reaction, temperature-controlled stirring and the like, and the performance stability and construction adaptability of the slurry are ensured. The material provided by the invention has the advantages of low viscosity, high permeability, rapid curing, high strength and good environmental adaptability, can be widely applied to underground engineering leakage water treatment, and has the remarkable advantages of convenience in construction, environmental protection, economy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy-saving and environmentally friendly building materials, and in particular relates to a high-permeability grouting material for treating water leakage and a preparation method thereof. Background Art

[0002] In underground engineering and tunnel construction, water leakage has always been a major problem in engineering construction and maintenance. Water leakage not only affects the stability and durability of engineering structures, but may also lead to environmental problems such as groundwater pollution and surface subsidence. Therefore, it is particularly important to develop and apply efficient water leakage control materials and technologies.

[0003] Traditional methods for water leakage control mainly include mechanical plugging, chemical grouting and physical plugging. Mechanical plugging usually uses materials such as concrete and mortar for repair, but this method is not effective when facing fine cracks or complex geological conditions. Chemical grouting injects chemical slurry into cracks or gaps, and uses the solid body generated by its chemical reaction to plug the leakage channel. Common chemical grouting materials include cement, water glass, polyurethane, acrylate, etc. However, these materials also have some limitations in practical applications: Cement-based slurry: Cement slurry has a high viscosity and is difficult to penetrate into small cracks. It is easily diluted by groundwater in highly permeable formations, resulting in poor reinforcement effect. In addition, the cement slurry has a long setting time and low construction efficiency.

[0004] Water glass slurry: Water glass (sodium silicate) slurry has good permeability, but the silicate gel formed after solidification has low strength and is easily washed away under high water pressure, resulting in a short-lasting water blocking effect.

[0005] Polyurethane slurry: Polyurethane material has good elasticity and adhesion, can adapt to the slight deformation of the structure, and is suitable for plugging deformation joints and cracks. However, its cost is high, and its reaction speed slows down in low temperature environment, which affects the construction progress.

[0006] Acrylate slurry: Acrylate materials have attracted attention due to their low viscosity and high permeability, and can penetrate into small cracks to form a high-strength consolidation body. However, the proportion and construction process of acrylate materials have a great influence on their performance and need to be precisely controlled.

[0007] With the continuous development of engineering construction, especially the construction of large underground projects such as high-speed railways, subways, underground pipe galleries, etc., the requirements for water leakage control materials are getting higher and higher. The research and development and application of high-permeability grouting materials have become the key to solving this problem. High-permeability grouting materials need to have the following characteristics: Low viscosity: ensure that the slurry can penetrate into small cracks and pores.

[0008] High permeability: Able to diffuse effectively in high permeability formations to form a continuous consolidated body.

[0009] Quick response: It can cure quickly during construction, reducing construction time.

[0010] High strength: The cured material has sufficient compressive and tensile strength to ensure long-term water blocking effect.

[0011] Environmental protection: The material should be non-toxic and harmless and meet environmental protection requirements.

[0012] Strong adaptability: able to adapt to different geological conditions and temperature changes.

[0013] At present, there are some high-permeability grouting materials on the market, but these materials still have some problems in practical application, such as: complex material ratio: the proportion of each component needs to be precisely controlled, and the slightest carelessness may lead to a decrease in material performance.

[0014] The construction process has high requirements: it requires a professional construction team and equipment, and the construction is difficult.

[0015] Higher cost: The cost of high-performance materials is often higher, which increases the economic burden of the project.

[0016] Environmental adaptability: The performance of some materials is unstable in low or high temperature environments, which affects the construction effect.

[0017] Therefore, developing a grouting material that can meet the high permeability requirements, is easy to operate during construction, has moderate cost, is environmentally friendly and has good durability has become a research hotspot in the current field of underground engineering water leakage control. The present invention aims to provide a high permeability grouting material and a preparation method for water leakage control by optimizing the material formula and preparation process, so as to solve the above problems and improve the construction efficiency and quality of underground engineering. Summary of the invention

[0018] Problem to be solved

[0019] Water leakage in underground engineering and tunnel construction has always been a difficult problem in engineering construction and maintenance. Traditional water leakage treatment methods (such as mechanical plugging, chemical grouting, etc.) are not effective when facing fine cracks or complex geological conditions. There are the following main problems: Cement-based slurry: high viscosity, poor permeability, difficult to fill small cracks, and easily diluted by groundwater.

[0020] Water glass slurry: low strength and short-lasting water blocking effect.

[0021] Polyurethane slurry: high cost and slow reaction speed in low temperature environment.

[0022] Acrylate slurry: Performance is greatly affected by the ratio and process and requires precise control.

[0023] With the construction of large-scale underground projects (such as subways, high-speed railways, and underground pipeline galleries), higher requirements are placed on grouting materials, including low viscosity, high permeability, rapid curing, high strength, environmental protection, and strong adaptability.

[0024] Technical Solution

[0025] To solve the above problems, the present invention adopts the following technical solutions.

[0026] A high-permeability grouting material for treating water leakage diseases comprises the following raw materials, measured by weight: 64-90 parts of 525 type sulfoaluminate cement, 15-30 parts of fly ash, 4-8 parts of isophorone diisocyanate, 10-20 parts of polyvinyl acetate, and 8-20 parts of nano-modifier.

[0027] Preferably, the raw materials are as follows, measured in parts by weight: 70-80 parts of 525 type sulfoaluminate cement, 18-25 parts of fly ash, 4-8 parts of isophorone diisocyanate, 15-20 parts of polyvinyl acetate, and 14-18 parts of nano-modifier.

[0028] Preferably, the raw materials are as follows, measured in parts by weight: 75 parts of 525 type sulfoaluminate cement, 22 parts of fly ash, 6 parts of isophorone diisocyanate, 18 parts of polyvinyl acetate, and 16 parts of nano-modifier.

[0029] Preferably, the parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide. The density of fly ash is 2.43 g / cm 3 The fly ash particles are relatively fine and the particle size is uneven, ranging from about 200-400μm.

[0030] Preferably, the CAS number of isophorone diisocyanate is 4098-71-9, and the relative density is 1.049; the CAS number of polyvinyl acetate is 9003-20-7, and the relative density is 1.18.

[0031] Preferably, the preparation method of the nano modifier is as follows: heating the polyurethane emulsion to 40-50°C and continuously stirring to make it stably dispersed; slowly dripping 0.1-0.3 times the weight of polyvinyl alcohol into the polyurethane emulsion under stirring, adding 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles after the dripping is completed, and continuing to stir for 30-60 minutes to fully disperse the particles into the polyurethane emulsion; reacting at 80-90°C for 30-60 minutes, slowly cooling to room temperature, and standing, and finally naturally air-drying.

[0032] The parameters of polyurethane emulsion (PU-601) are as follows: Appearance: milky white translucent liquid. Density: 1.3g / cm 3 Solid content: 60%. Viscosity: ≤60s (PU-601). PH value: 8.0±1 (PU-601). Particle size: 200nm. Yellowing: Level 4 (PU-601). Elongation: ≈1000% (PU-601). Resilience: 100% (PU-601). Cold resistance: no bursting at -25℃ (PU-601). Film formation: soft, transparent, smooth to the touch (PU-601).

[0033] Among them, diammonium hydrogen citrate nanoparticles CAS number: 3012-65-5, molecular weight: 226.19, appearance: white granular, with ammonia odor, density: 1.48g / mL, melting point: 185℃, water solubility: soluble in water, slightly soluble in ethanol, acidity and alkalinity: the aqueous solution is weakly acidic.

[0034] Carboxyethylsilanetriol sodium salt granules CAS number: 18191-40-7, molecular weight: 174.16, appearance: white granules, density: 1.17g / mL, water solubility: forms a stable aqueous solution.

[0035] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0036] Mixing reaction: Place weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 3-5 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 5-10 minutes, control the temperature to 25-35°C, obtain slurry, then filter the slurry with a filter screen or filter bag for standby use.

[0037] Beneficial Effects

[0038] Compared with the prior art, the beneficial effects of the present invention are as follows: the introduction of the nano-modifier significantly improves the performance of the high permeability grouting material, and its beneficial effects are mainly reflected in the following aspects, which are analyzed in combination with the reaction mechanism occurring inside the nano-modifier itself.

[0039] The nano-modifier is composed of the following ingredients and is prepared by a specific process: Polyurethane emulsion: As a base material, it provides good dispersibility and bonding properties.

[0040] Polyvinyl alcohol: Enhances dispersion stability and improves the fluidity of slurry.

[0041] Diammonium hydrogen citrate nanoparticles: provide filling effect and reduce porosity.

[0042] Carboxyethylsilanetriol sodium salt particles: enhance interfacial bonding and improve anti-seepage performance.

[0043] During the preparation process, nanoparticles are dispersed in polyurethane emulsion and react chemically with other components at high temperature to form a stable functional nanocomposite material. Specifically, through the synergistic effect of polyurethane emulsion and polyvinyl alcohol, nanoparticles are evenly dispersed in the liquid phase, avoiding agglomeration, forming a stable slurry system, and improving the fluidity and penetration of the slurry.

[0044] The active groups on the surface of diammonium hydrogen citrate nanoparticles (such as -NH4 + ) physically adsorbs or chemically combines with components in the slurry (such as cement hydration products). The carboxyl group (-COOH) and silane group (Si-OH) in the sodium salt of carboxyethylsilanetriol particles can form chemical bonds with the cement matrix, enhance the interfacial bonding between the slurry and the substrate, and improve the mechanical properties and durability of the solidified body. At high temperatures, the functional groups in the polyurethane emulsion (such as -NCO) undergo cross-linking reactions with polyvinyl alcohol or other components to form a three-dimensional network structure, increase the density of the solidified body, reduce porosity, and enhance impermeability and compressive strength.

[0045] Nano-modifiers significantly improve the comprehensive performance of grouting materials through internal reactions: they improve the fluidity and permeability of the slurry, enabling it to effectively fill small cracks and pores.

[0046] The density and interface bonding strength of the solidified body are enhanced, thereby significantly reducing the permeability coefficient and improving the anti-permeability performance.

[0047] The microstructure of the solidified body is optimized to give it higher compressive strength, toughness and durability.

[0048] These beneficial effects make the grouting material of the present invention have wider applicability and better construction performance in the treatment of water leakage in underground projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a scanning electron microscope image of the slurry prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0050] The present invention is further described below in conjunction with specific embodiments.

[0051] Unless otherwise defined, the technical and scientific terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The weight units mentioned below may be replaced by kilograms when specifically implemented.

[0052] Example 1

[0053] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 64 parts of 525 type sulfonaluminate cement, 30 parts of fly ash, 4 parts of isophorone diisocyanate, 20 parts of polyvinyl acetate, and 8 parts of nano modifier.

[0054] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0055] The CAS number of isophorone diisocyanate is 4098-71-9, and the relative density is 1.049; the CAS number of polyvinyl acetate is 9003-20-7, and the relative density is 1.18.

[0056] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 40°C and continue stirring to make it stably dispersed; slowly add 0.1 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 300 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 80°C for 60 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0057] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0058] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 3 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 5 minutes, control the temperature to 35°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0059] Example 2

[0060] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 90 parts of 525 type sulfonaluminate cement, 15 parts of fly ash, 8 parts of isophorone diisocyanate, 10 parts of polyvinyl acetate, and 20 parts of nano modifier.

[0061] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0062] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0063] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0064] Preferably, the preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 50°C and continue stirring to make it stably dispersed; slowly add 0.3 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 60 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 90°C for 30 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0065] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0066] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 5 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 10 minutes, control the temperature to 25°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0067] Example 3

[0068] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 70 parts of 525 type sulfonaluminate cement, 25 parts of fly ash, 4 parts of isophorone diisocyanate, 20 parts of polyvinyl acetate, and 14 parts of nano modifier.

[0069] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0070] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0071] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0072] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 40°C and continue stirring to make it stably dispersed; slowly add 0.1 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 30 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 80°C for 30 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0073] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0074] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 3 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 5 minutes, control the temperature to 25°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0075] Example 4

[0076] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 80 parts of 525 type sulfonate aluminate cement, 18 parts of fly ash, 8 parts of isophorone diisocyanate, 15 parts of polyvinyl acetate, and 18 parts of nano modifier.

[0077] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0078] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0079] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0080] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 50°C and stir continuously to make it stably dispersed; slowly add 0.3 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 60 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 90°C for 60 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0081] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0082] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 5 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 10 minutes, control the temperature to 35°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0083] Example 5

[0084] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 75 parts of 525 type sulfonaluminate cement, 22 parts of fly ash, 6 parts of isophorone diisocyanate, 18 parts of polyvinyl acetate and 16 parts of nano modifier.

[0085] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0086] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0087] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0088] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 45°C and continue stirring to make it stably dispersed; slowly add 0.2 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 50 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 85°C for 50 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0089] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0090] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 4 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 8 minutes, control the temperature to 30°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0091] Comparative Example 1

[0092] The high permeability grouting material for treating water leakage comprises the following raw materials in parts by weight: 75 parts of 525 type sulfonated aluminate cement, 22 parts of fly ash, 18 parts of polyvinyl acetate and 16 parts of nano modifier.

[0093] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0094] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0095] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 45°C and continue stirring to make it stably dispersed; slowly add 0.2 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 50 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 85°C for 50 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0096] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0097] Mixing reaction: Place the weighed 525 type sulfon-aluminate cement, fly ash and nano-modifier in a mixer, then add 20 times the weight of 525 type sulfon-aluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 4 minutes, control the temperature not to exceed 40°C, then filter the slurry with a filter screen or filter bag and set aside.

[0098] Comparative Example 2

[0099] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 75 parts of 525 type sulfonaluminate cement, 22 parts of fly ash, 6 parts of isophorone diisocyanate, and 16 parts of nano modifier.

[0100] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0101] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0102] The preparation method of the nano modifier is as follows: heat the polyurethane emulsion to 45°C and continue stirring to make it stably dispersed; slowly add 0.2 times the weight of polyvinyl alcohol to the polyurethane emulsion under stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, continue stirring for 50 minutes, so that the particles are fully dispersed in the polyurethane emulsion; react at 85°C for 50 minutes, slowly cool to room temperature, and let it stand, and finally dry it naturally with air.

[0103] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0104] Mixing reaction: Place the weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, continue stirring for 4 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula dosage to the above dispersion, continue stirring for 8 minutes, control the temperature to 30°C, obtain slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0105] Comparative Example 3

[0106] The high permeability grouting material used for the treatment of water leakage diseases comprises the following raw materials, measured by weight: 75 parts of 525 type sulfonaluminate cement, 22 parts of fly ash, 6 parts of isophorone diisocyanate, and 18 parts of polyvinyl acetate.

[0107] The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

[0108] The CAS number of isophorone diisocyanate is 4098-71-9 and the relative density is 1.049.

[0109] The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.18.

[0110] The method for preparing a high-permeability grouting material for water leakage treatment comprises the following steps: weighing and pre-treating raw materials: accurately weighing raw materials according to weight to ensure that all powder raw materials are dry and free of lumps; if there is agglomeration or does not meet the particle size requirements, sieving or grinding is performed.

[0111] Mixing reaction: Place the weighed 525 type sulfoaluminate cement and fly ash in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 4 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 8 minutes, control the temperature to 30°C, obtain a slurry, and then filter the slurry with a filter net or filter bag for standby use.

[0112] Product performance test: (1) Fluidity test

[0113] The fluidity test is used to evaluate the flow and filling ability of the grouting slurry. It is a key indicator of whether the grouting material can penetrate smoothly into cracks and pores. The specific test methods and standards are as follows: Fluidity determination: Use a standard fluidity cone to measure the expansion diameter of the fresh slurry on a vibration table. Place the fluidity cone on a horizontal glass plate with the cone mouth facing down, and add slurry into the cone; slowly lift the cone to allow the slurry to flow and expand naturally on the glass plate; start the vibration table, stop after 15 vibrations, and measure the maximum diameter and vertical diameter of the slurry expansion. The fluidity is the average of the two diameters and is expressed in millimeters (mm).

[0114] Marsh cone outflow time measurement: Marsh cone outflow time is another indicator to characterize the fluidity of grouting slurry. During the test, pour the slurry into the Marsh cone, wait for it to flow out naturally, and record the time required for 1500mL of slurry to flow out.

[0115] Table 1 Fluidity test results

[0116] Fluidity (mm): Example group: The fluidity is between 172.3-179.6 mm, indicating that the slurry has good fluidity and is suitable for penetrating into small cracks. Comparative Example group: The fluidity is significantly reduced, especially in Comparative Example 3, which is only 153.1 mm, indicating that after removing key components (such as nano-modifiers), the fluidity of the slurry is greatly reduced, which is not conducive to construction.

[0117] Marsh cone outflow time (s): Example group: The outflow time is between 26.4-27.3 seconds, showing low viscosity characteristics, which is conducive to the rapid injection of slurry into cracks. Comparative example group: The outflow time is significantly increased, especially comparative example 3 reaches 35.9s, indicating that the slurry viscosity is too high, which is not conducive to penetration construction.

[0118] Comprehensive evaluation: Example 5 performed best, with the highest fluidity (179.6 mm) and the shortest Marsh cone outflow time (26.4 s), indicating that it has excellent fluidity after formula optimization.

[0119] The performance degradation of the comparative group indicates that the key components (isophorone diisocyanate, polyvinyl acetate, and nano-modifier) ​​are essential to maintain low viscosity and high fluidity of the slurry.

[0120] (2) Penetration testing

[0121] Permeability reflects the diffusion and filling capacity of grouting materials in different media. The permeability of materials can be comprehensively evaluated by conducting grouting experiments in standard sand columns or clay media.

[0122] Standard sand column permeability test: Select standard sand with particle size distribution and compaction density that meet the requirements, prepare a cylindrical sand column with a diameter of 10 cm and a height of 50 cm, and conduct a grouting experiment without lateral pressure: arrange a grouting pipe at the bottom of the sand column, and slowly inject slurry until the slurry overflows from the top of the sand column. After the slurry solidifies, take out the sand column and cut it open to observe the diffusion range of the slurry. Permeability coefficient determination: The permeability of the sand column is tested before and after grouting, and the Darcy's law formula is used to calculate the change in permeability coefficient.

[0123] The parameters of standard sand are as follows: d10 (effective particle size): 0.15-0.30mm, that is, on the particle size distribution curve, the content of particles smaller than this particle size accounts for 10% of the total mass; d30: 0.35-0.55mm, that is, on the particle size distribution curve, the content of particles smaller than this particle size accounts for 30% of the total mass; d60 (limited particle size): 0.6-0.9mm, that is, on the particle size distribution curve, the content of particles smaller than this particle size accounts for 60% of the total mass. As can be seen from the above, the effective particle size d10 of standard sand is in the range of 0.15-0.30mm, and d60 is in the range of 0.6-0.9mm. The overall particle size range is narrow, and it belongs to medium sand.

[0124] Table 2 Permeability test results

[0125] Analysis and evaluation

[0126] Diffusion radius (cm): Example group: The diffusion radius is between 25-29 cm, all showing good penetration and diffusion capabilities, especially Example 5 reaches 29 cm, indicating that the material can effectively fill cracks and pores. Comparative Example group: The diffusion radius is significantly reduced, and Comparative Example 3 is only 15 cm, indicating that the material loses its good penetration and diffusion capabilities after removing the nano modifier.

[0127] Permeability coefficient: Example group: The permeability coefficient was significantly reduced to 3-5×10 -7 cm / s, indicating that the anti-permeability of the medium is greatly improved after grouting. Comparative group: The permeability coefficient is greatly increased, indicating that the material cannot effectively reduce the permeability of the medium after removing the key components.

[0128] Comprehensive evaluation: Example 5 performed best, with the largest diffusion radius (29 cm) and the lowest permeability coefficient, indicating that it has excellent permeability and anti-permeability effects. The performance degradation of the comparative group once again verified the importance of key components. In particular, after removing the nano-modifier, the diffusion radius and anti-permeability of comparative example 3 were significantly reduced.

[0129] According to the experimental results, it is recommended to use the formula of Example 5 in actual projects, and strictly control the addition amount of key components to ensure that the grouting material has good construction adaptability and long-term anti-seepage effect. Figure 1 As shown, it shows the state of the slurry prepared in Example 5 after 28 days of curing (curing temperature: 25°C, curing humidity: 95%), and a dense microstructure can be seen.

[0130] The removal of isophorone diisocyanate (IPDI) in comparative example 1 resulted in a significant decrease in material performance, the mechanism of which can be attributed to the following points: The strength of the solidified body is reduced: Without IPDI, the slurry cannot form an efficient cross-linked network, and the mechanical properties of the solidified body are significantly reduced. The internal structure of the solidified body becomes loose, resulting in a weakening of its bearing capacity. The impermeability is reduced: The cross-linking effect of IPDI can significantly reduce the internal porosity of the material. After removal, a dense structure cannot be formed in the solidified body, the porosity increases, and the permeability coefficient increases. In the permeability test, the permeability coefficient of comparative example 1 is much higher than that of Example 5. The durability of the material is weakened: IPDI has excellent resistance to ultraviolet light and chemical corrosion. After removal, the material is more susceptible to environmental factors (such as water, acid, alkali, and ultraviolet light) during long-term use and deterioration. After removing IPDI, the microstructure of the solidified body of the slurry changes significantly: the pores increase: in the absence of a cross-linking reaction, microcracks and pores are easily generated during the curing process of the slurry. Weakened interfacial bonding force: The synergistic effect of IPDI and polyvinyl acetate can enhance the bonding force between particles. After removal, the bonding force in the interface transition zone is insufficient, resulting in an uneven overall structure.

[0131] The removal of polyvinyl acetate in Comparative Example 2 resulted in a significant decrease in material performance, the mechanism of which can be attributed to the following points: Reduced slurry fluidity: After the lack of polyvinyl acetate, the slurry loses the lubrication effect of the molecular chain, the internal friction increases, and the fluidity decreases significantly. As shown in the fluidity test, the fluidity of Comparative Example 2 is 165 mm, which is much lower than that of Example 5 (179.6 mm), and the Marsh cone outflow time increases to 31.7 s, indicating that the viscosity of the slurry increases, which is not conducive to construction. Weakened interfacial bonding force of the solidified body: After the removal of polyvinyl acetate, the interfacial bonding force between the slurry and the substrate is significantly reduced, resulting in a weak bond between the particles inside the solidified body. This will directly affect the compressive strength and durability of the solidified body. Increased porosity: The lack of the polyvinyl acetate network structure causes more micropores to be generated during the curing process, resulting in a decrease in density. In the permeability test, the permeability coefficient of Comparative Example 2 is significantly higher than that of Example 5, indicating that the anti-permeability performance is seriously reduced. Decreased toughness and crack resistance: Without the flexible polyvinyl acetate molecular chain, the solidified body is prone to cracks due to shrinkage or external loads, thereby reducing stability in long-term use. After removing polyvinyl acetate, the microstructure of the slurry solidified body changes significantly: Uneven particle distribution: Without the auxiliary dispersion function of polyvinyl acetate, cement particles and fly ash are prone to agglomeration in the slurry. Increased porosity: Due to the lack of a uniformly distributed network structure, the internal porosity of the solidified body increases. Deterioration of the interface transition zone: The interface bonding force between the slurry and the substrate is weakened, making the transition zone a weak link.

[0132] The removal of the nanomodifier in Comparative Example 3 resulted in a significant decrease in the performance of the grouting material, and its mechanism can be attributed to the following points: Reduced slurry fluidity: Mechanism: The functional polyurethane emulsion and polyvinyl alcohol in the nanomodifier can improve the lubrication performance of the slurry. After removal, the friction force in the slurry increases and the fluidity decreases. Performance: In the fluidity test, the fluidity of Comparative Example 3 is 153.1 mm, which is much lower than that of Example 5 (179.6 mm), and the Marsh cone outflow time is significantly increased to 35.9 s (26.4 s for Example 5). Decreased density of the solidified body: Mechanism: Nanoparticles have a filling effect and can reduce the micropores inside the material. After removal, the porosity in the solidified body increases, resulting in a decrease in density. Performance: In the permeability test, the permeability coefficient of Comparative Example 3 is too high, resulting in a significant decrease in its anti-permeability performance. Weakened interfacial bonding force: Mechanism: The nanomodifier enhances the interfacial bonding force between the slurry and the substrate through chemical reaction or physical adsorption. After removal, the interfacial bonding force is insufficient, resulting in a decrease in the strength of the solidified body. Performance: The diffusion radius is only 15 cm (29 cm in Example 5), indicating that the penetration ability and filling effect of the slurry are significantly reduced. Deterioration of mechanical properties: Mechanism: The nanoparticles form a network structure during the curing process, which helps to improve the compressive strength and toughness. After removal, the internal structure of the solidified body is loose, and the compressive strength is significantly reduced. Performance: The solidified body is prone to cracks or damage, and is not suitable for complex engineering environments. After removing the nano-modifier, the microstructure of the slurry solidified body changes significantly: The porosity increases: In the absence of nano-particle filling, more micropores appear inside the solidified body. Uneven particle distribution: In the absence of functional polyurethane emulsion and polyvinyl alcohol, cement particles and fly ash are easy to agglomerate, resulting in uneven material distribution. Deterioration of the interface transition zone: The interface bonding force is weakened, making the transition zone a weak link.

[0133] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field of energy-saving and environmentally friendly building materials technology to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope determined by the claims submitted by the present invention.

Claims

1. A high permeability grouting material for water leakage treatment, characterized in that: In parts by weight, the following raw materials are included: 525 type sulfonated aluminate cement: 64-90 parts, Fly ash: 15-30 parts, Isophorone diisocyanate: 4-8 parts, Polyvinyl acetate: 10-20 parts, Nano modifier: 8-20 parts.

2. The high permeability grouting material for water leakage treatment according to claim 1 is characterized in that: In parts by weight, the following raw materials are included: 525 type sulfonated aluminate cement: 70-80 parts, Fly ash: 18-25 parts, Isophorone diisocyanate: 4-8 parts, Polyvinyl acetate: 15-20 parts, Nano modifier: 14-18 parts.

3. The high permeability grouting material for water leakage treatment according to claim 2 is characterized in that: In parts by weight, the following raw materials are included: 525 type sulfonated aluminate cement: 75 parts, Fly ash: 22 parts, Isophorone diisocyanate: 6 parts, Polyvinyl acetate: 18 parts, Nano modifier: 16 parts.

4. The high permeability grouting material for water leakage treatment according to claim 1 is characterized in that: The parameters of fly ash are as follows: 45% by mass content of silicon dioxide, 35% by mass content of aluminum oxide, 15% by mass content of iron oxide, and the balance is calcium oxide.

5. The high permeability grouting material for water leakage treatment according to claim 1 is characterized in that: The CAS number of isophorone diisocyanate is 4098-71-9, and the relative density is 1.049; The CAS number of polyvinyl acetate is 9003-20-7 and the relative density is 1.

18.

6. The high permeability grouting material for water leakage treatment according to claim 1, characterized in that: The preparation method of the nano modifier is as follows: Heat the polyurethane emulsion to 40-50°C and continue stirring to make it stably dispersed; slowly add 0.1-0.3 times the weight of polyvinyl alcohol to the polyurethane emulsion while stirring, and after the addition is completed, add 0.1 times the weight of diammonium hydrogen citrate nanoparticles and 0.2 times the weight of carboxyethylsilanetriol sodium salt particles of the polyurethane emulsion, and continue stirring for 30-60 minutes to fully disperse the particles in the polyurethane emulsion; react at 80-90°C for 30-60 minutes, slowly cool to room temperature, and let it stand, and finally air dry naturally.

7. The method for preparing the high permeability grouting material for water leakage treatment according to claim 1, comprising the following steps: Raw material weighing and pretreatment: weigh the raw materials accurately according to weight to ensure that all powder raw materials are dry and free of lumps; if there are agglomerates or the particle size requirements are not met, sieve or grind them; Mixing reaction: Place weighed 525 type sulfoaluminate cement, fly ash and nano modifier in a mixer, then add 20 times the weight of 525 type sulfoaluminate cement in water, then slowly add polyvinyl acetate under stirring conditions, initially disperse to form a dispersion, continue stirring for 3-5 minutes, control the temperature not to exceed 40°C, then slowly add isophorone diisocyanate according to the formula amount to the above dispersion, continue stirring for 5-10 minutes, control the temperature to 25-35°C, obtain slurry, then filter the slurry with a filter screen or filter bag for standby use.

Citation Information

Patent Citations

  • Polymer wet-mixed mortar

    CN109761557A

  • Water-dispersion-resistant polyurethane rigid foam grouting water-stop reinforcing material and preparation method thereof

    CN111763416A

  • Acidic gas flooding self-adaptive thickening nano-particles as well as preparation method and application thereof

    CN113801646A

  • High-permeability nano modified acrylate grouting material and preparation method thereof

    CN116217783A

  • Concrete slurry modifier for reducing slurry permeability

    CN117819866A

Cited By

  • Supersulfurized ardealite slag grouting material with high impermeability and preparation method of persulfurized ardealite slag grouting material

    CN120554076A